New biomarkers and multiplex tests for diagnosis of aggressive prostate cancer and therapy management - Milan Kral; Daniela Kurfurstova; Pavel Zemla; Martin Elias; Jan Bouchal; Jan Bouchal (Frontiers in Oncology)
Despite improving diagnostic possibilities, the incidence of prostate cancer is increasing, but we are not able to reduce the mortality rate. While PSA, 4K score, PCA3 and other urinary markers, ExoDX, SelectMDX, Confirm MDx or MiPS tests are used to identify potential prostate cancer carriers, Decipher, Prolaris or Oncotype DX tests are used to assess the aggressiveness of proven cancer in order to stratify patients for early or delayed treatment. More modern forms of treatment for advanced disease include second-generation antiandrogens and PARP inhibitors. By assessing genetic mutations (e.g. BRCA1, BRCA2 genes, single nucleotide polymorphism) or the presence of splice variants of the androgen receptor (ARV7), we are able to identify patients in whom the planned treatment may be expected to be ineffective and thus choose other treatment modalities. In the present review article, we offer a comprehensive overview of current diagnostic tests that find application in the diagnosis of early and advanced prostate cancer.